Hepatitis C virus deep sequencing for sub-genotype identification in mixed infections: A real-life experience. (February 2018) - del Campo, José A.; Parra-Sánchez, Manuel; Figueruela, Blanca; García-Rey, Silvia; Quer, Josep; Gregori, Josep; Bernal, Samuel; Grande, Lourdes; Palomares, José C.; Romero-Gómez, Manuel
Highlights: Routine strategies for hepatitis C virus (HCV) genotyping have several limitations. Deep sequencing methods can solve this problem. Accurate determination of viral genotypes and subtypes would allow optimal patient management and the most effective therapy. Mixed infections may represent a key factor for efficient therapy. Patients infected with more than one HCV genotype (mixed infection) can be detected only by deep sequencing methods. These patients can fail treatment with direct-acting antiviral agents, hence next-generation sequencing methods are highly recommended in clinical practice. Abstract: Background: The effectiveness of the new generation of hepatitis C treatments named direct-acting antiviral agents (DAAs) depends on the genotype, subtype, and resistance-associated substitutions present in individual patients. The aim of this study was to evaluate a massive sequencing platform for the analysis of genotypes and subtypes of hepatitis C virus (HCV) in order to optimize therapy. Methods: A total of 84 patients with hepatitis C were analyzed. The routine genotyping methodology for HCV used at the study institution (Versant HCV Assay, LiPA) was compared with a deep sequencing platform (454/GS-Junior and Illumina MiSeq). Results: The mean viral load in these HCV patients was 6.89 × 10 6  ± 7.02 × 10 5 . Viral genotypes analyzed by LiPA were distributed as follows: 26% genotype 1a (22/84), 55% genotype 1b (46/84), 1% genotype 1 (1/84), 2.5% genotype 3 (2/84), 6% genotype 3a (5/84), 6% genotype 4a/c/d (5/84). When analyzed by deep sequencing, the samples were distributed as follows: 27% genotype 1a (23/84), 56% genotype 1b (47/84), 8% genotype 3a (7/84), 5% genotype 4d (4/84), 2.5% genotype 4f (2/84). Six of the 84 patients (7%) were infected with more than one subtype. Among these, 33% (2/6) failed DAA-based triple therapy. Conclusions: The detection of mixed infection could explain some treatment failures. Accurate determination of viral genotypes and subtypes would allow optimal patient management and improve the effectiveness of DAA therapy.